UPAYA GURU PPKn DALAM MEMBENTUK MORALITAS SISWA - Ade Millatus saadiyah; Agung Setia Budi (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2019)
This mini Thesis examines effort teacher education pancasila and civic in estabilishment of morality student of class VIII MTs Shiddiq Al Farizy Baros. This research was backround by the importance of estabilishment of moral student, because observe from deviance away from etnic and manner. Moral is foundation for implant to student for be generation who is a noble. Effort teacer education pancasila and civic in estabilishment of morality student of class VIII MTs Shidiq Al Farizy Baros thisi research descriptive,qualitative, namely data, obtained likr result observe, interview, observe, dokumentation. This reserch indicates that factors that because student of MTS Shiddiq Al Farizy Baros pembiasaan, keteladanan, discus, speech, simulation ass well ass reward and punishment. Resulf from this research indicated with change in attitude and behaviour of students toward better with reflect habit obey regulation teacher when learning in the class.